The effectivity of science manipulative based smart class virtual laboratory to improve science process skill - Andriani, Aldina Eka; Ary, Deasylina Da; Asih, Sri Sami (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2024)
This study aims to determine the effectiveness of using a smart class virtual laboratory based on Science Manipulative Learning with the dimensions of the Pancasila student profile through PhET Simulation and OLABS on the science process skills of PGSD students. This research is an experimental study with a research design of a nonequivalent control group design and sampling technique by purposive sampling. The sample in the study was PGSD students in semester 2 of the SD Science Laboratory course in Group J and M totaling 50 people. Data collection techniques used tests and non-tests. Tests are used to measure science process skills through Pre-test and Post-test. Non-test is used to observe student activities during learning using a smart class virtual laboratory based on science manipulative learning through PhET Simulation with observation sheets and questionnaires. Data analysis techniques use the Normality Test of gain (Normalized-Gain), Homogeneity Test, Test the effect between variables using a Paired Sample T-test, and the effect between variables using an Independent T-test. The results and analysis can conclude that the application of Smart Class Virtual Laboratory Based on Science Manipulative Learning Dimensioned Pancasila Student Profile Through PhET Simulation and OLABS effectively improves science process skills. This is evidenced by the pretest and posttest N-Gain test values, which obtained a score of 0.64 with a moderate increase in the category.